Strategi Humas Kepemerintahan Dan Iklim Investasi (Studi Deskriptif Kualitatif Strategi Humas Kabupaten Boyolali Mendorong Kebijakan Boyolali Pro Investasi) - Suprihatini, Tri; , Drs. JokoSutarso, S.E, M.Si (2016)
Tri Suprihatini, L100110048, GOVERNMENT RELATIONS STRATEGY AND INVESTMENT CLIMATE (Descriptive Study of Public Relations Strategies Qualitative Boyolali Boyolali Pro Encouraging Investment Policy) Thesis, Communication Studies, Faculty of Communication and Informatics, University of Muhammadiyah Surakarta, 2016. Government Public Relations served as a disseminator of information on the broad policies and activities in institutions of his government. PR Regency Boyolali Boyolali policy encouraging investment Pro uses a strategic approach to community Boyolali and relations to the mass media. The purpose of this study was to determine what strategy to use public relations to drive forward progress Boyolali Regency Boyolali Pro investment policies. This study was descriptive qualitative data collection techniques used were observation and interviews, documentation. These results indicate that PR Boyolali regency using a strategic approach to the mass media which perform public relations news both locally and nationally on television, radio, newspapers, press conference and press release. By doing so, the PR can deliver its message more broadly in order to attract investors in Boyolali which will be beneficial to society and development in Boyolali. Keywords: PR Strategy, Investment Climate.